Health equity: evidence synthesis and knowledge translation methods - Welch, Vivian A; Petticrew, Mark; O'Neill, Jennifer; Waters, Elizabeth; Armstrong, Rebecca; Bhutta, Zulfiqar A; Francis, Damian; Koehlmoos, Tracey Perez; Kristjansson, Elizabeth; Pantoja, Tomas; Tugwell, Peter (Université d'Ottawa | University of Ottawa, 2013)
At the Rio Summit in 2011 on Social Determinants of Health, the global community recognized a pressing need to take action on reducing health inequities. This requires an improved evidence base on the effects of national and international policies on health inequities. Although systematic reviews are recognized as an important source for evidence-informed policy, they have been criticized for failing to assess effects on health equity.